Kingdom of the Netherlands-Aruba : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report, 1999)
This 1999 Article IV Consultation highlights that Aruba's real GDP grew at an annual rate of some 3 percent in 1998, while inflation remained subdued at about 2 percent. Comparable rates of satisfactory growth and low inflation have characterized the island's development since the mid-1990s, following a period of double-digit growth when an investment boom in the hotel sector brought about the transformation of Aruba into a tourism-based economy. The outlook for satisfactory growth and low inflation had been threatened, however, by an undue relaxation of fiscal policy in 1996 and continued laxity through mid-1998.